PERSEPSI MAHASISWA PENDIDIKAN EKONOMI TERHADAP KOPERASI MAHASISWA (KOPMA) UNIVERSITAS RIAU - Armala, Elysa Riska; Suarman, Suarman; Syakdanur, Syakdanur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine economic education student perception’stoward Kopma of Riau University. Problem Formulation in this research is HowEconomics Education Student Perception’s toward Kopma of Riau University? This is adescriptive study with a quantitative approach which aims to describe the results by thenumbers. The sampling technique using stratified random sampling, taken at randombased on the level (2010, 2011, 2012). Data collection techniques in this study is thequestionnaire technique which there are 35 items statement. Data obtained from 61respondents as the sample study, sources from class 2012 amounted to 36 people, classof 2011 amounted to 18 people and the class of 2010 amounted to 7 people. The resultshowed that economic education student perception’s toward Kopma of Riau Universityclassified as poor, with an average percentage of 40.9%. From the six indicators, thehighest average percentage is on Attention indicator, which amounted to 47.5%. Theseresults indicate that the Attention indicator has a great influence in shaping studentperception’s toward Kopma of Riau University. Kopma administrators can improve thequality of Kopma from these points, such as by improving services to students so thatthe attention of students increased to Kopma and also by increasing socialization andinformation as posible.Keywords: Perception of Students, Economic Education